Thermal management for prevention of failures of lithium ion battery packs in electric vehicles: A review and critical future aspects. Issue 3 (4th May 2020) - Aswin Karthik, Chandrasekaran; Kalita, Pankaj; Cui, Xujian; Peng, Xiongbin
Abstract: The major concerns with Lithium‐ion batteries failures are temperature rise and temperature non‐uniformity during adverse operating conditions like fast charging/discharging and extreme ambient conditions (extreme hot/cold weather). These problems lead to safety issues like thermal runaway of the battery pack. To negate these issues and to ensure better performance of the battery pack, battery thermal management system (BTMS) is adopted in EVs. The prominent BTMSs are air‐based BTMS, liquid‐based BTMS and phase change based BTMS. This paper collates various thermal management issues and numerous cooling methods developed to mitigate these problems and throws light on some of the research gaps on recovery and utilization of low‐grade heat generated in the battery pack.